P062: Impact of pharmacist-led medication review in the emergency department on downstream health services utilization. (2nd June 2016) - Hohl, C.M.; Wickham, M.E.; McGrail, K.; Sobolev, B.G.
Abstract : Introduction: Adverse drug events are a leading cause of Emergency Department (ED) visits and unplanned admissions. Up to 50% are misdiagnosed in the ED and on hospital wards leading to treatment delays. Our main objective was to evaluate the effect of pharmacist-led medication review in high-risk ED patients on the number of days in-hospital. Our hypothesis was that early pharmacist-led medication review may reduce the number of days spent in-hospital.Methods: We evaluated a quality improvement program that was implemented in three British Columbian EDs. During a 12-month period, nurses identified consecutive patients at high-risk for adverse drug events using a clinical decision rule integrated into triage algorithms. Clinical pharmacist research assistants enrolled consecutive eligible high-risk patients, and systematically allocated them to medication review or control. In the intervention group, pharmacists collected best possible medication histories, reviewed medications for appropriateness and adverse drug events, and communicated review results to patients and physicians. In the control group, nurses collected best-possible medication histories, and physicians referred patients to the ED pharmacist as needed. Ongoing care was determined by physicians who were not blinded to group allocation, but were unaware of the evaluation. We assessed outcomes using administrative health databases. The primary outcome was the number of days spent in-hospital over 30 days. We used inverse propensity score weighted regression modeling to assess the relationship between medication review and health outcomes. The sample size was limited by the duration of the quality improvement program.Results: Among 10, 807 patients 6, 416 received medication review in the ED and 4, 391 usual care. The groups were balanced in terms of baseline characteristics. The median number of hospital days was 0.48 days (95% confidence interval [CI] 0.00-0.96) less in the medication review group compared to usual care (p=0.058). The difference was 0.60 days (95% CI 0.06-1.17; p=0.03) less among patients under 80 years old. There was no effect on ED revisits, number of admissions and readmissions, or mortality.Conclusion: Medication review was associated with a trend in reduced hospital-bed utilization. While limited by lack of randomization, our evaluation suggests that ED pharmacists may impact subsequent resource utilization.